Mastering digital electronics an ultimate guide to logic circuits and advanced circuitry - Ward, Hubert Henry (Apress, 2024)
Discover the essential knowledge and practical skills to excel in the dynamic field of digital electronics with "Mastering Digital Electronics." From the fundamentals of diode resistor logic to unraveling the intricacies of TTL and CMOS logic gates, this book takes you on a journey through the evolution of digital electronics. Starting with the humble SR latch and progressing to the revolutionary JK flip flop that powers today's computer technology, you'll gain a solid foundation in binary arithmetic, Boolean algebra, and the representation and optimization of digital circuits. The book gives a firm understanding of digital electronics, then moves on to using standard design methods, such as state diagrams, to design everyday logic circuits such as counters, shift registers, PISO, and SIPO registers. It delves into how to design some challenging digital circuits such as a crossroad set of traffic lights with a pelican crossing and how to use the 555 timer to control a variety of applications. At every stage of the book, you will be learning how to use TINA version 12, an industry standard ECAD and many of its functions. Moreover, the book ventures into using the software to simulate and so confirm all the circuits you design. For readers interested in advancing to the practical implementation of the circuits discussed, the book provides opportunities to design PCB circuit boards for selected circuits using the software. This book will suit any student of digital electronics at any level and provide them with essential reference material for them to start a career in digital electronics.
Includes index
Keywords: Digital electronics; Électronique numérique